2009
DOI: 10.1172/jci38201
|View full text |Cite
|
Sign up to set email alerts
|

Foxa1 and Foxa2 regulate bile duct development in mice

Abstract: The forkhead box proteins A1 and A2 (Foxa1 and Foxa2) are transcription factors with critical roles in establishing the developmental competence of the foregut endoderm and in initiating liver specification. Using conditional gene ablation during a later phase of liver development, we show here that deletion of both Foxa1 and Foxa2 (Foxa1/2) in the embryonic liver caused hyperplasia of the biliary tree. Abnormal bile duct formation in Foxa1/2-deficient liver was due, at least in part, to activation of IL-6 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 56 publications
5
125
0
Order By: Relevance
“…Although the origin of hamartomas as well as the mechanism of their development in the Fbxw7-deficient liver are currently unclear, transient activation of Notch proteins as a result of Fbxw7 loss may lead to a shift in cell differentiation from hepatocytes to cholangiocytes, and the generation of such abnormally differentiated cells might confer a predisposition to hamartoma development that is realized if the cells undergo an additional gene mutation. Mice lacking both Foxa1 and Foxa2 were recently shown to display a similar liver phenotype (hyperplasia of the biliary tree) (56). However, neither differentiation of hepatocytes nor Notch signaling were affected in Foxa1/2-deficient mice, whereas hyperactivation of Notch signaling seems to be attributable to the bile duct hamartoma in Fbxw7-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the origin of hamartomas as well as the mechanism of their development in the Fbxw7-deficient liver are currently unclear, transient activation of Notch proteins as a result of Fbxw7 loss may lead to a shift in cell differentiation from hepatocytes to cholangiocytes, and the generation of such abnormally differentiated cells might confer a predisposition to hamartoma development that is realized if the cells undergo an additional gene mutation. Mice lacking both Foxa1 and Foxa2 were recently shown to display a similar liver phenotype (hyperplasia of the biliary tree) (56). However, neither differentiation of hepatocytes nor Notch signaling were affected in Foxa1/2-deficient mice, whereas hyperactivation of Notch signaling seems to be attributable to the bile duct hamartoma in Fbxw7-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Post-developmentally, there are many examples of where prior binding by FoxA factors enables the subsequent binding by hormone receptors and other DNA-binding proteins (Gao et al 2003;Carroll et al 2005;Zhang et al 2005;Li et al 2009Li et al , 2012bPihlajamaa et al 2014), as previously covered in greater detail (Zaret and Carroll 2011). The mammalian circadian clock is driven by the CLOCK and BMAL1 transcription factors that rhythmically bind to nucleosomal target sites, promote incorporation of the histone variant H2A.Z, and enable the subsequent binding of other transcription factors (Menet et al 2014).…”
Section: Pioneer Factors In Cell Programming During Developmentmentioning
confidence: 99%
“…Il6 mRNA, a cytokine regulating Th1, Th2, and Th17 cell differentiation (51,52), was increased 4.6-fold in Foxa2 Δ/Δ mice. Recent studies demonstrated that Foxa2 bound to the Il6 promoter and suppressed Il6 expression in liver (53). Because multiple Th1-associated genes are altered in the Foxa2 Δ/Δ mice, it is presently unclear which play the dominant roles in the observed phenotype.…”
Section: Th2 Cytokine-dominated Inflammation Postdeletion Of Foxa2 Inmentioning
confidence: 99%